2001
DOI: 10.1093/pcp/pce012
|View full text |Cite
|
Sign up to set email alerts
|

Technical Advance: Reduction of Fe(III)-Chelates by Mesophyll LeafDisks of Sugar Beet. Multi-Component Origin and Effects of FeDeficiency

Abstract: The characteristics of the Fe(III)-chelate reductase activity have been investigated in mesophyll disks of Fe-sufficient and Fe-deficient sugar beet leaves. The Fe(III)-chelate reductase activity of mesophyll disks was light dependent and increased markedly when the epidermis was removed. Iron(III)-citrate was photo-reduced directly by light in the absence of plant tissue. Total reductase activity was the sum of enzymatic mesophyll reduction, enzymatic reduction carried out by organelles exposed at the disk ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
38
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 31 publications
3
38
0
1
Order By: Relevance
“…Physiological studies also support the idea of a reduction-based iron acquisition system in leaf cells as well as organelles (8). Fe(III) chelate reductase activities have been detected in leaf disks (9,10) and leaf protoplasts (11,12), and inhibition of iron transport into barley chloroplasts by an Fe(II) chelator implicated Fe(III) reduction in plastid transmembrane iron influx (13). Indeed, Fe(II) transport across the chloroplast inner envelope has been detected in vitro with inner envelope vesicles (14).…”
supporting
confidence: 55%
“…Physiological studies also support the idea of a reduction-based iron acquisition system in leaf cells as well as organelles (8). Fe(III) chelate reductase activities have been detected in leaf disks (9,10) and leaf protoplasts (11,12), and inhibition of iron transport into barley chloroplasts by an Fe(II) chelator implicated Fe(III) reduction in plastid transmembrane iron influx (13). Indeed, Fe(II) transport across the chloroplast inner envelope has been detected in vitro with inner envelope vesicles (14).…”
supporting
confidence: 55%
“…However, in our case, the levels of iron were similar in both green leaves from NO-treated plants and chlorotic leaves from untreated plants. It is known that leaves can develop chlorosis even at higher iron concentrations than those needed to render green leaves, chlorophyll biosynthesis, and chloroplast development (Kosegarten et al, 1999;González-Vallejo et al, 2000;Larbi et al, 2001). That is because an important proportion of the iron is unavailable because it remains insoluble in the apoplast of mesophyll cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the features of the chemical reduction and the multistep transport of iron inside the cell and inside the chloroplast are still largely unknown. It was suggested that some steps of the internal transport system may be impaired by the iron deficiency itself (González-Vallejo et al, 2000;Larbi et al, 2001). There is also evidence that iron could be immobilized and accumulated as inactive forms in the leaf (Morales et al, 1998;Kosegarten et al, 1999), and this would explain why in many cases chlorotic leaves from iron-deficient plants have total 1 This work was supported by the Consejo Nacional de Investigaciones Científicas y Técnicas (grant no.…”
mentioning
confidence: 99%
“…While plasmamembrane bound enzyme ferric chelate reductase (FCR) reduced the ferric form of iron into ferrous before entry into the cells (Brüggemann et al 1993). Further, activity of this enzyme was reported to be controlled by light, pH and several other factors (González-Vallejo et al 2000;Larbi et al 2001). These type of findings indicated that higher amount of iron penetration occurred with Fe-sulphate than other sources (Table 3).…”
Section: Discussionmentioning
confidence: 99%